Where can your passport take you? Teaching citizenship, mobility, and identity. Issue 3 (2nd July 2016) - Lawless, Brandi; Tejada, Jimena; Tejada, Xantal
Abstract : Courses: Intercultural Communication, Culture and Conflict, International Conflict and Alliance Building Objectives: After completing this single-class activity, students should be able to (1) describe the concepts of identity, citizenship, and mobility; (2) empathize with the everyday struggles of students who hold citizenship outside of their "homeland"; and (3) explain how intersectionality influences an individual's ability to traverse national borders.